Directions of Urban Development in the City of Kalar (1977-2024) (Raparin Journal of Humanities (RJH), 2025)
Nowadays, urban population growth is considered one of the most significant and touchy issues of city geography, because population growth directly affects planning and development of the cities. Moreover, it shows an important area of ​​the pillars of development. Therefore, in most cities in the Kurdistan region, the changes and population growth are taken into consideration. The purpose of this paper is to illustrate economic, social, and prosperity scientifically. We can claim that the large amount of population has caused most of the issues that affect cities nowadays. A number of factors have influenced this dilemma, such as natural increase of population and migration, especially the migration of people from rural areas to the cities. The lack of an advanced plan to prevent migration and regulate the rapid growth that occurs in cities is to be mentioning. At the same time, this growth led to some conclusions; the rapid expansion of the cities can be considered the key factor. This expansion mostly is at the expense of agricultural and suburban lands.This paper deals with the directions of urban development between the years 1970 - 2024 in Kalar. For this purpose, the research depended on the results of data and information obtained from official censuses. The research consists of two main parts and several discussions, in which the growth, the demographic changes, and the growth of population growth of Kalar, depending on the official census, are discussed. The rapid increase in population growth and the relations of these changes with the historical events of the region are illustrated.